Factors influencing turning and its relationship with falls in individuals with Parkinson's disease. - Fang-Yu Cheng; Yea-Ru Yang; Chung-Jen Wang; Yih-Ru Wu; Shih-Jung Cheng; Han-Cheng Wang; Ray-Yau Wang (PLoS ONE)
Background Falls are a major problem for people with Parkinson's disease (PD). Many studies indicate that more than 50% of people with PD have difficulty in turning that may lead to falls during daily activities. The aims of this study were to identify the relationship between turning performance and falls, and to determine the factors that influence turning performance. Methods This study examined 45 patients with idiopathic PD (Hoehn and Yahr stage 1-3) using a battery of tests, including 180° turn time, balance, and muscle strength. The levels of disease severity and freezing of gait were also measured. The number of falls in the past 6 months was recorded. Results Sixteen out of forty-five participants experienced falls in the past 6 months. A receiver operating characteristic curve showed that turn time was highly related to falls [more affected side: sensitivity = 0.81, specificity = 0.79, area under the curve (AUC) = 0.83; less affected side: sensitivity = 0.88, specificity = 0.76, AUC = 0.83]. The most important factor influencing turn time was balance ability (both sides: p = 0.000) according to the regression model. Correlations between turn time and dynamic balance were further established with reaction time, movement velocity, endpoint excursion, and maximal excursion of the LOS (limits of stability) test. Conclusion The time needed to complete a 180° turn during the SQT (step/quick turn) test is a good index to differentiate fallers from non-fallers in persons with PD. Turn time is most influenced by balance. Furthermore, balance control, especially in an anterior or sideways direction, is important for turning performance.